Educating the scholar practitioner in organization development - Colwill, Deborah A. (Emerald Publishing Limited : Information Age Publishing, 2012)
Organization Development (OD) is a young social science. Little has been written on the intentional development of OD professionals. As a young field of inquiry it is important to understand how the future leaders of the field of OD are being developed. The focus of this work explores the education of scholar practitioners in OD. The research upon which this document is based examined the impact that professional research doctoral programs (affiliated with the field of OD) had on the learning and professional development of select doctoral graduates. Alumni reported important elements of their educational experience that contributed to their professional and personal growth. The nature of these educational elements suggest processes or methods of teaching that may be transferable to training OD professionals in a broader context outside of higher education. Even more directly this research provides well informed feedback to administrators and faculty of professional research doctorate programs from the alumni about their educational experience. This feedback could be used to advance both program and course development in universities that offer these types of degrees. The intended audience of this work includes practitioners of OD, professors of OD and management, faculty and administrators of doctoral education, talent management and leadership development professionals, and adult educators.
Keywords: Organizational change -- Study and teaching (Higher); Organizational behavior -- Study and teaching (Higher); Business & Economics -- General.; Business innovation.; Business and Management.; elektronické knihy; electronic books